2005
DOI: 10.1002/app.21199
|View full text |Cite
|
Sign up to set email alerts
|

Novel, positively charged membrane from a blending, crosslinking, and coagulation procedure

Abstract: A novel, positively charged membrane was prepared through a blending, crosslinking, and coagulation procedure in which poly(N,N-dimethylaminoethyl methacrylate) (PDM) and polyacrylonitrile (PAN) were used as the functional and substrate component, respectively. Because 1,4-dibromobutane (DBT) was used as the crosslinker and quaternizing agent, PDM was crosslinked and quaternized simultaneously. The effects of PDM content, polymer concentration, and additive dosage of the casting solution on the membrane perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Tethering (i.e., covalently bonding) QAS to a surface to achieve long-term activity has been previously investigated. Surfaces coated with QAS-containing polymers have been shown to be very effective in killing a wide range of microorganisms such as Gram-positive and Gram-negative bacteria, yeasts, and molds. Various material architectures such as self-assembled monolayers, polyelectrolyte layers, and hyper-branched dendrimers have been used to produce biocidal surfaces. While surface tethered QAS moieties have been shown to exhibit antimicrobial properties, the mechanism of kill must be different than that described for QAS in solution because of diffusion limitations of tethered QAS. Kugler et al recently reported on the mechanistic aspects of tethered QASs and showed the existence of a charge-density threshold for surfaces bearing tethered QAS groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tethering (i.e., covalently bonding) QAS to a surface to achieve long-term activity has been previously investigated. Surfaces coated with QAS-containing polymers have been shown to be very effective in killing a wide range of microorganisms such as Gram-positive and Gram-negative bacteria, yeasts, and molds. Various material architectures such as self-assembled monolayers, polyelectrolyte layers, and hyper-branched dendrimers have been used to produce biocidal surfaces. While surface tethered QAS moieties have been shown to exhibit antimicrobial properties, the mechanism of kill must be different than that described for QAS in solution because of diffusion limitations of tethered QAS. Kugler et al recently reported on the mechanistic aspects of tethered QASs and showed the existence of a charge-density threshold for surfaces bearing tethered QAS groups.…”
Section: Introductionmentioning
confidence: 99%
“…Tethering (i.e., covalently bonding) QAS to a surface to achievelong-termactivityhasbeenpreviouslyinvestigated. [13][14][15] Surfaces coated with QAS-containing polymers have been shown to be very effective in killing a wide range of microorganisms such as Gram-positive and Gram-negative bacteria, yeasts, and molds. [15][16][17] Various material architectures such as self-assembled monolayers, polyelectrolyte layers, and hyper-branched dendrimers have been used to produce biocidal surfaces.…”
Section: Introductionmentioning
confidence: 99%